Patient-specific molecular alterations are associated with metastatic clear cell renal cell cancer progressing under tyrosine kinase inhibitor therapy - Dietz, Steffen; Sültmann, Holger; Du, YueJun; Riediger, Anja Lisa; Volckmar, Anna-Lena; Stenzinger, Albrecht; Schlesner, Matthias; Jäger, Dirk; Hohenfellner, Markus; Duensing, Stefan; Grüllich, Carsten; Pahernik, Sascha (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.18200 Steffen Dietz, Holger Sültmann, YueJun Du, Eva Reisinger, Anja Lisa Riediger, Anna-Lena Volckmar, Albrecht Stenzinger, Matthias Schlesner, Dirk Jäger, Markus...